Polymer systems for solid pharmaceuticals (eXPRESS Polymer Letters)
Macromolecular components of pharmaceuticals represent a segment of small quantity but high value within the polymer market. The knowledge built in these systems act as driving force for other polymer fields. Their conventional role, the coating and bonding, has been extended recently due to new challenges.